Byproduct from Triphala Extraction as Tannin and Rutin Sources for Production of Gallic Acid, Isoquercetin and Quercetin by Solid-State Fermentation - Teerin Chysirichote; Pattarabhorn Pakaweerachat (Chemical and Biochemical Engineering Quarterly, 2022)
Byproduct from Triphala extraction process (BTP) was studied as a substrate for gallic acid, isoquercetin and quercetin production by Aspergillus niger fermentation in this research. The results showed that BTP was a good source of tannin and rutin. Neverthe less, the activity of A. niger on BTP as a sole substrate was very low. Supplementing nitro gen sources was found to be a key to enhancing conversion of tannin to gallic acid, and rutin to isoquercetin or isoquercetin and quercetin. BTP with 0.75 % sodium nitrate was sug gested to be an optimal supplemented nitrogen source for the production of gallic acid and isoquercetin in this research, which yielded the highest contents of 61.62.16 mg g -1 DS and 3.270.29 mg g -1 DS , respectively. In addition, the highest extraction yields of gallic acid, isoquercetin and quercetin were obtained by an ultrasoundassisted extraction using methanol as an extraction solvent as 12.242.12 mg g -1 DS which was around 0.5 time higher than the one without ultrasoundassisted extraction (8.841.12 mg g -1 DS ).
Keywords: Tannin, Tannase and Anticancer Activities; Phytochemicals and Antioxidant Activities; Food Science and Nutritional Studies